Importance of hardness and toughness in ceramic armour - Goh, Wei Liang (2019)
Extensive studies on ceramic armour had been conducted since the late 1960s, laying down the foundations for ceramic armour studies today. However, most of the work done has focussed on small calibre projectiles; i.e. 7.62 mm projectile, with limited work on long rod projectiles. Of these, there is a lack of studies that investigate relationships between hardness and fracture toughness of ceramic armour module components. On top of that, there is no consensus in the community on the relationship between ceramic hardness and its ballistic performance. The overall objective of this study was therefore to understand the influence of hardness and fracture toughness of ceramic armour module components on the ballistic performance of ceramic armour against long rod projectiles.